Culture of animal cells : A manual of basic techniques and specialized applications - Freshney, R. Ian; Freshney, R. Ian (New Jersey, John Wiley & sons, ins., 2010)
This is the sixth edition of the leading text in the basic methodology of cell culture, worldwide. Rigorously revised, it features updates on specialized techniques in stem cell research and tissue engineering; updates on molecular hybridization, somatic cell fusion, hybridomas, and DNA transfer; new sections on vitrification and Organotypic Culture, and new chapters on epithelial, mesenchymal, neurectodermal, and hematopoietic cells; germs cells/stemcells/amniocytes; and non-mammalian/avian cells. It is written for graduate students, research and clinical scientists, and technicians and laboratory managers in cell and molecular biology labs and genetics labs.
Appendix 595-662p.; References 663-716p.; Index 717-732p.